PENGARUH PENERAPAN E-FILLING, KUALITAS PELAYANAN, SOSIALISASI PAJAK DAN SANKSI PAJAK TERHADAP KEPATUHAN WAJIB PAJAK ORANG PRIBADI (Studi Kasus Pada Kantor Pelayanan Pajak Pratama Boyolali) - Subiyanto, Muhamad Nofa; Suryana, Alean Kistiani Hegy; Triatmaja, Nur Asih; Sultan (EKOBIS, 2025)
This study aims to determine how the effect of e-filling implementation, service quality, tax socialization and tax sanctions on individual taxpayer compliance at KPP Pratama Boyolali. Data collection techniques with a questionnaire with a sample of 111 respondents using purposive sampling. The method used is quantitative with analysis regression linier multiplied. Testing data instruments with validity and reliability tests, analyzing data with normality tests, heteroscedasticity tests, autocorrelation tests and multicollinearity tests. Hypothesis testing used the t test by looking at the significance if below 0.05 there is an influence. The significance value of 0.048 <0.05 the application of e-filing has a positive effect on taxpayer compliance so it can be concluded that H1 is accepted, a significance value of 0.004 <0.05 it can be said that H2 is accepted because service quality has a positive effect on taxpayer compliance, a significance value of 0.000 <0.05 tax socialization has a positive effect on taxpayer compliance and hypothesis H3 is accepted, a significance value of 0.643> 0.05 it is clear that tax sanctions have no positive effect on taxpayer compliance, so H4 is rejected.